The Borgias. The first season [videorecording (DVD)] - Jordan, Neil, 1950- (Showtime Entertainment, 2011)
Rodrigo Borgia becomes Pope Alexander VI, propelling him, his two sons Cesare and Juan, and his daughter, Lucrezia, to become the most powerful and influential family of the Italian Renaissance.